Development of deep red–emitting CaBiVO5:Pr3+ phosphor for multifunctional optoelectronic applications. Issue 11 (29th June 2021) - Kaur, Harpreet; Jayasimhadri, Mula
Abstract: Orthorhombic Pr 3+ ‐doped calcium bismuth vanadate (CBV: Pr 3+ ) phosphors have been synthesized successfully via a citrate‐gel method. The single‐phase formation of CBV: Pr 3+ phosphor has been endorsed by X‐ray diffraction (XRD) analysis. The scanning electron microscopy (SEM) image reveals dense‐particle packaging with the quasi‐spherical shape for the prepared CBV: Pr 3+ phosphors. Under blue light excitation, CBV: Pr 3+ phosphors exhibit intense red emission bands located at 608 and 656 nm wavelengths, overlapping with the absorption spectrum of PR phytochrome, which is present in plants. To achieve the maximum red intensity, the Pr 3+ ion concentration is optimized to be 1.25 mol% in the CBV host, after which the emission intensity ceases due to concentration quenching. Dexter's theory disclosed the possibility of d‐d multipolar interaction among Pr 3+ ions at higher concentrations of Pr 3+ ions in the CBV host. The CIE coordinates are found to be positioned in the pure red region for CBV: Pr 3+ phosphor and in the proximity of red‐emitting commercial phosphor. The temperature‐dependent spectral studies manifest substantial thermal stability of the as‐synthesized phosphor. All the studies mentioned above specify the tremendous potentiality of thermally stable CBV: Pr 3+ phosphor in agricultural lighting and w‐LED applications.